Age as a risk factor for orthostatic hypotension induced by the levodopa challenge test in patients with Parkinson's disease: Results from a single-center trial. Issue 9 (3rd March 2023) - Su, Dan; Su, Yanling; Xu, Baolei; Chhetri, Jagadish K.; Chan, Piu
Abstract : Background: Hypotension can occur in patients receiving levodopa (L-dopa) treatment for parkinsonism. However, only few studies have focused on the characteristics of orthostatic hypotension (OH) induced by the L-dopa challenge test (LCT). This study aimed to investigate the characteristics and influencing factors of LCT-induced OH in a relatively large sample of patients with Parkinson's disease (PD). Methods: Seventy-eight patients with PD without a previous diagnosis of OH underwent the LCT. Blood pressure (BP) in the supine and standing positions was measured before and 2 hours after the LCT. If diagnosed with OH, the patients' BP was monitored again 3 hours after the LCT. The clinical features and demographics of the patients were analyzed. Results: Eight patients were diagnosed with OH 2 hours after the LCT (median dose of 375 mg L-dopa/benserazide; incidence = 10.3%). One patient without symptoms had OH 3 hours after the LCT. Compared with patients without OH, patients with OH had lower 1- and 3-minutes standing systolic BP and 1-minute standing diastolic BP at baseline and 2 hours after the LCT. Patients in the OH group were of older age (65.31 ± 4.17 years vs 59.74 ± 5.55years) and had lower Montreal Cognitive Assessment scores (17.5 vs 24) and higher L-dopa/benserazide levels (375 [250, 500] mg vs 250 [125, 500] mg). Older age markedly increased the odds of having LCT-induced OH (odds ratio, 1.451; 95% confidence interval, 1.055–1.995; P = .022). Conclusions: LCT increased the odds of OH in non-OH PD, causing symptomatic OH in 10.3% of patients in our study, thereby raising safety concerns. Increase in age was observed to be a risk factor for LCT-induced OH in PD patients. A study with a larger sample size is warranted to confirm our results. Trial registration number: Clinical Trials Registry under ChiCTR2200055707. Date of registration: January 16, 2022.